Quality of Life After Laparoscopic Adjustable Gastric Banding Using the Baros and Moorehead-Ardelt Quality of Life Questionnaire II - Myers, Jonathan A. (Society of Laparoendoscopic Surgeons, 2006)
OBJECTIVES: The goal of weight reduction surgery is not only to decrease excess weight, but also to improve obesity related comorbidities and quality of life (QoL). Until now, few studies have utilized objective methods to evaluate all of these issues. Hereafter, using the newly developed Moorehead-Ardelt Quality of Life Questionnaire II (M-A QoLQ II) incorporated into the Bariatric Analysis and Reporting Outcome System (BAROS), we report our results for patients undergoing laparoscopic adjustable gastric banding (LAGB). METHODS: M-A QoLQ II questionnaires were sent to patients undergoing LAGB at a single institution. Nonresponders were contacted by a second mailing and telephone calls. The respondents’ data were scored according to BAROS guidelines. RESULTS: Data from 67 patients with a mean follow-up of 27 months (22–35) were analyzed. Mean age was 43.8 years (range, 21 to 68) with a mean preoperative body mass index (BMI) of 49.8 kg/m(2) (range, 38.4 to 67.7). Mean postoperative BMI was 37.1 kg/m(2) (range, 23.0 to 53.4) for a mean excess weight loss (EWL) of 53.2% (range, −7.5% to 108.6%). According to the BAROS scoring system, 8 patients (12%) were classified as failures, 13 patients (19%) had fair, 24 (36%) had good, 13 (19%) had very good, and 9 (13%) had excellent results. There was considerable improvement in patient's comorbidities, and positive scores for self-esteem, and activity level. CONCLUSIONS: The use of the M-A QoLQ II is an efficient method of assessing the success of bariatric surgery. Widespread use of the questionnaire would assist in standardizing reporting of results following bariatric surgery. Our results suggest that LAGB may lead to excellent results with regards to resolution of comorbidities, improvement in QoL, and overall weight loss.